Globalisasi MSDM sebagai Strategi Peningkatan Kualitas Pendidikan: Refleksi Studi Banding Yayasan Al-Amanah Sunter Agung, Jakarta Utara ke SK Cyberjaya, Malaysia - Islami, Hani; Azizatulhadhro, Neng Lulu (Innovative: Journal Of Social Science Research, 2025)
Globalization demands that educational institutions manage human resources (HR) more professionally and adaptively. This study aims to reflect on the learning experiences of Yayasan Al-Amanah Sunter Agung Jakarta Utara through a benchmarking visit to SK Cyberjaya Malaysia as a strategy to improve education quality. This research employs a descriptive qualitative approach through in-depth interviews with teachers. The findings reveal that SK Cyberjaya implements a well-structured HR management system, technology integration, and strong character-building values. Yayasan Al-Amanah has begun applying clearer task distribution, simple digital media usage, and a more collaborative work culture. Key challenges include limited access to technology, budget constraints, and resistance to change. This study concludes that adapting global practices to local contexts requires gradual strategies that take into account available resources and existing work culture.